Estrogenic effect of Medicago sativa L (alfalfa) hydroalcoholic extract in albino rats ovariectomized - Bezada, Sandra G. (2014)
This study aimed to demonstrate the estrogenic properties of the hydroalcoholic extract of Medicago sativa L (alfalfa) in albino rats ovariectomized (OVX). Were used 48 albino Sprague Dawley rats of 200 to 250 g, 8 weeks of age, of whom 40 underwent surgical removal of both ovaries, following the technique of bilateral ovariectomy on the flank. After the post-operative were divided into six groups and hydroalcoholic extract was administered orally under the following scheme of work: Group 1 negative control: (OVX), vehicle of the extract 2mL/kg; Group 2 positive control: (OVX), estradiol subcutaneous 3 µg/kg; Group 3, 4 y 5: (OVX) more extract 100, 500 and 1000 mg/kg, respectively; and Group 6: not OVX control the surgical procedure (SHAM). The treatment lasted 14 days and was evaluated the body weight, uterine weight, changes of oestrus by vaginal smears and hormonal profile analysis. Were observed increase in body weight, uterine weight, in estradiol levels and changes in vaginal cytology. Was conclude that the hydroalcoholic extract of Medicago sativa L (alfalfa) showed estrogenic effect by modifying the parameters evaluated.